GREEN MARKETING STRATEGIES AND CONSUMER BEHAVIOR: A SYSTEMATIC LITERATURE REVIEW - Ma'sum, Muhammad Fahmi; Azhar, Noviridhany Maulana; Jamaluddin, Jamaluddin (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This research examines the influence of green marketing strategies on consumer purchasing decisions and brand loyalty through a systematic review of existing literature. With increasing awareness of environmental issues, consumers are increasingly choosing products that demonstrate a commitment to sustainability. This research uses a Systematic Literature Review (SLR) approach with the PRISMA method to identify, filter and analyze relevant articles from various academic databases. The analysis results show that green product attributes, transparent marketing communications, and the company's commitment to social responsibility contribute significantly to increasing consumer trust and loyalty. However, greenwashing practices can undermine that trust. These findings provide important insights for companies in designing effective and authentic green marketing strategies to increase competitiveness in an increasingly sustainability-oriented market.